2021
DOI: 10.1097/01.asw.0000753196.64470.6a
|View full text |Cite
|
Sign up to set email alerts
|

Should We Scan Hidradenitis Suppurativa Patients? A Systematic Review of Radiologic Findings

Abstract: OBJECTIVE To bring awareness and close gaps between dermatologists and radiologists about the contribution of imaging techniques for diagnosis, treatment, and follow-up of hidradenitis suppurativa (HS). DATA SOURCES Investigators searched the PubMed database for articles on HS and radiology techniques. STUDY SELECTION Databases were searched up to December 2018. The query retrieved 257 publications, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(210 reference statements)
1
4
0
Order By: Relevance
“…Its major limitation of USG in HS is its inability to visualize lesions less than 0.1 mm 32 and the difficulty in differentiating between acne, pilonidal sinus, and folliculitis lesions. 13,33 This seems consistent with our series in which a patient diagnosed with folliculitis and acne vulgaris showed features identical to HS on USG. Other limitations include impediments in imagining extrasphincteric and suprasphincteric extensions attributable to poor beam penetration.…”
Section: Limitationssupporting
confidence: 91%
See 2 more Smart Citations
“…Its major limitation of USG in HS is its inability to visualize lesions less than 0.1 mm 32 and the difficulty in differentiating between acne, pilonidal sinus, and folliculitis lesions. 13,33 This seems consistent with our series in which a patient diagnosed with folliculitis and acne vulgaris showed features identical to HS on USG. Other limitations include impediments in imagining extrasphincteric and suprasphincteric extensions attributable to poor beam penetration.…”
Section: Limitationssupporting
confidence: 91%
“…Other limitations include impediments in imagining extrasphincteric and suprasphincteric extensions attributable to poor beam penetration. 13 We encountered this limitation while evaluating perianal lesion in a suspect HS patient, although we could rule out HS using USG. Extensive fibrosis has also been shown to reduce the utility of USG, even intraoperatively.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two articles comprised comprehensive reviews on the usefulness of various radiological techniques in diagnosing and managing HS. The first review determined that CT imaging was considered inferior to PET imaging for HS; however, PET had limitations in visualizing anatomic localization and lesion extensions [37]. The second review concluded that there was no apparent advantage in imaging HS lesions with FDG-PET/CT scans, as these scans can result in false positives when attempting to identify metastatic cancer [38].…”
Section: Resultsmentioning
confidence: 99%
“…However, no standardized method currently exists for identifying subclinical lesions. The evidence powering this review comprises 63 studies discussing HS and various radiologic imaging techniques, and includes randomized controlled trials, systematic reviews, books, observational studies, case reports, and case series [37].…”
Section: Comprehensive Reviewsmentioning
confidence: 99%